Analysis of the Effect of Good Corporate Governance, Company Size and Liquidity on Dividend Policy and Company Value with Profitability as an Intervening Variable in State-Owned Companies Listed on the IDX 2011 – 2019 - Zuhandi; Iskandar Muda; Sirojuzilam (Institute of Computer Science (IOCS), 2021)
Research aims to analyze the influence of good corporate governance , company size, liquidity and profitability as factors affecting the company's dividend policy and the value of the state-owned enterprises listed on the Indonesia Stock Exchange Period 2011-2019. The type of data used is secondary data and the data analysis technique used is Panel Data Regression Analysis using STATA software. The results of the study with an alpha level of five percent showed that GCG had no significant effect on profitability, while company size had no significant positive effect and liquidity had a significant positive effect on profitability. GCG and company size have a negative and insignificant effect on dividend policy, while liquidity and profitability have a significant positive effect on dividend policy. Furthermore, GCG and liquidity have a negative and insignificant effect on firm value, while company size has a significant negative effect on firm value. positive and significant impact on firm value. The results of path analysis I show that GCG has an indirect negative effect and company size indirectly has a positive effect on dividend policy through profitability, while liquidity does not have an indirect effect on dividend policy through profitability. Path II analysis, company size and liquidity indirectly have a positive effect and GCG indirectly has a negative effect on firm value through profitability